Introduction: Cancer a Global Challenge and Role of Angiogenesis in Cancer - Mukherjee S.; Madamsetty V.S. (My University, 2025)
Cancer is a global cause of mortality and morbidity resulting in deaths of millions (Siegel et al. in CA Cancer J Clin 72:7–33, 2022, [1]). © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.